2022
DOI: 10.1155/2022/3181133
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Dose Apatinib Improves the Prognosis of Patients with Recurrent High-Grade Gliomas

Abstract: Objective. To evaluate the efficacy, safety, and prognostic value of low-dose apatinib in combination with temozolomide in the treatment of primary or recurrent high-grade gliomas (HGGs). Methods. A retrospective analysis of patients with postoperative and recurrent HGGs treated in our hospital from April 1, 2018, to April 30, 2020. Patients should be treated by combination therapy (surgery + radiotherapy + chemotherapy). Patients who received apatinib combined with temozolomide chemotherapy were allocated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…2C and D ). Among all studies, there were two studies with significant deviation ( 26 , 27 ), and after excluding these two studies, the I 2 -value was reduced to 2.3% ( Fig. 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2C and D ). Among all studies, there were two studies with significant deviation ( 26 , 27 ), and after excluding these two studies, the I 2 -value was reduced to 2.3% ( Fig. 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicate entries and abstracts, 15 studies were selected. After removing any studies that did not meet the subject and inclusion criteria, 10 studies were finally included in the comprehensive analysis (14)(15)(16)(21)(22)(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%